Entertainment Event Management And Improving Gen Z Literacy In Event Organizers - Setiawan, Rudi; Syahputra, Ahmad Reynaldi; Khumayah, Siti; Erawati, Dedet (Jurnal Polisci, 2025)
Currently, there are many festival events organised in Indonesia. However, most of the events organised only focus on delivering entertainment and do not focus on the essence of the ideas that want to be conveyed to the participants of an event, which of course can include all topics that are educational and informative. Pekan Sastra is one of the festival events held based on the lack of interest in literacy. This study aims to identify communication strategies in event management aimed at increasing Gen Z literacy in the implementation of literary week in Cirebon. This research explains the management of entertainment events and the improvement of Gen Z literacy in organising events. This research uses descriptive empirical research with a qualitative approach. The data sources used consist of secondary data and primary data. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis was carried out by reducing data, reading data and drawing conclusions. This research applies the event management theory proposed by Goldblatt in 2013, which consists of Research, Design, Planning, Coordination, and Evaluation. The results of this study indicate that event management has not run optimally, especially in terms of planning and coordination related to the implementation schedule that has not been flexible. This condition causes female participants who are students to have difficulty in obtaining permission from parents, and there is a lack of coordination with volunteers. In running an event, the event organiser needs careful coordination and preparation so that the event can be managed more effectively and efficiently.